PENGEMBANGAN LKPD BERBASIS STEM (SCIENCE, TECHNOLOGY, ENGINEERING, AND MATHEMATICS) TERINTEGRASI TRI N UNTUK MENINGKATKAN KETERAMPILAN BERPIKIR KRITIS PESERTA DIDIK - Winarsih Winarsih; Ana Fitrotun Nisa (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
This research aims to design and produce Student Activity Sheets (LKPD) based on STEM (Science Technology Engineering and Mathematics) integrated with Tri N on magnetic material. The research teaching materials used are research and development type. The subjects in this research were material experts, teaching materials experts, fellow teachers, and class VI students at SDN 2 Rowokele, Rowokele District, Kebumen Regency. Data collection was carried out using instruments in the form of interview guides, questionnaires, observation sheets and validation. Data analysis uses quantitative and qualitative descriptive analysis. The design of Tri N's integrated STEM-based LKPD was carried out using the ADDIE instructional development model, namely through the Analysis, Development, Implementation and Evaluation stages because in this model each stage is revised until a better LKPD product is obtained. The results of the research show that the design of Tri N's integrated STEM-based LKPD based on the assessment of material experts obtained an average percentage of 95.65% with appropriate criteria, the assessment of teaching material experts obtained an average percentage of 79% with appropriate criteria, the assessment of fellow teachers obtained an average percentage of average 79.78%. The results of using Tri N's integrated STEM-based LKPD designed to improve critical thinking skills obtained an average score of 85.67% with the number of students who completed it being 27 people. Tri N's integrated STEM-based LKPD on magnetic material has been designed to obtain